Adinandra longipedicellata - Tanggaraju, S.; Tsen, S.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Adinandra longipedicellata is known only from Telupid and Beluran areas, Sabah. It is locally common in forest near river with ultramafic geology in Sabah. The estimated area of occupancy (AOO) and extent of occupancy (EOO) are 28 km2 and 497 km2 respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. The localities are within protected areas and there is no continuing decline. There are no major threat for this species. Therefore, it is assessed as Least Concern. Adinandra longipedicellata is endemic to Borneo, and confined to Sabah, Malaysia.